Texts in Context - Boucher, David. author. aut Link
X, 281 p.
Keywords: The methodology of the study of the history of political thought is an area of study which has occupied my interests for nearly a decade. I was introduced to the subject in University College, Swansea. My teachers there provided me with an excellent grounding in political studies. I am particularly indebted to Bruce Haddock, Peter Nicholson and W. H. Greenleaf. Professor Greenleaf was kind enough to supply me with a copy of his bibliography and copies of two of his unpublished papers. I continued to pursue my interest in methodology at the London School of Economics and Political Science. I am indebted to Ken Minogue and Robert Orr who taught me there. My greatest debt is to Dr. Joseph Femia ofthe University of Liverpool who devoted a great deal of time to considering the arguments presented here. His criticisms and suggestions for improvement proved to be invaluable. I would also like to thank Alan Ryan for his general comments and encouraging advice. It would be remiss of me if I neglected to express my gratitude to Dewi Beynon who was my first teacher of politics. The research for this project was carried out in the following places; The British Library of Political Science, London; The Sidney Jones Library, University of Liverpool; The National Library of Scotland, Edinburgh; The Main Library, University of Edinburgh; The Arts and Social Science Library, University College, Cardiff; and the Bodleian Library, Oxford.